Investigation of factors influencing inpatient antibiotic prescribing decisions in the Veterans' Health Administration. Issue 1 (23rd June 2022) - Economos, Evan T.; Goedken, Cassie Cunningham; Sherlock, Stacey Hockett; Suda, Katie J.; Goetz, Matthew; Balkenende, Erin; Chasco, Emily E.; Scherer, Aaron M.; Goto, Michihiko; Perencevich, Eli N.; Schacht Reisinger, Heather; Livorsi, Daniel J.
Abstract: To investigate factors that influence antibiotic prescribing decisions, we interviewed 49 antibiotic stewardship champions and stakeholders across 15 hospitals. We conducted thematic analysis and subcoding of decisional factors. We identified 31 factors that influence antibiotic prescribing decisions. These factors may help stewardship programs identify educational targets and design more effective interventions.